2019
DOI: 10.3390/foods8070258
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocessed Production of Resveratrol-Enriched Rice Wine: Simultaneous Rice Wine Fermentation, Extraction, and Transformation of Piceid to Resveratrol from Polygonum cuspidatum Roots

Abstract: A new bioprocess to produce resveratrol-enriched rice wine was established and the effects of adding Polygonum cuspidatum root powder to rice wine fermentation were investigated. In this new process, piceid and resveratrol were extracted from P. cuspidatum roots to rice wine and piceid was converted to resveratrol by β-glucosidase during fermentation. After 10 days co-fermentation, rice wine with high levels of resveratrol was obtained, which contained ~14% (v/v) ethanol, 122 mg/L piceid, and 86 mg/L resveratr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Resveratrol mostly exists in dietary foods in a glycosylated form, which prevents resveratrol from enzymatic oxidation in the digestive tract, thus preserving its biological activity and overall stability. 148 , 149 However, intestine cells absorb only resveratrol aglycone via transepithelial diffusion with an absorption rate of approximately 75%. Pharmacokinetics studies have confirmed that resveratrol is rapidly and comprehensively metabolized through the intestine and liver, and the main glucoside and sulfate metabolites of resveratrol are produced through glucuronidation and sulfation.…”
Section: Pharmaceutical Properties Of Resveratrol Against Endometriosismentioning
confidence: 99%
“…Resveratrol mostly exists in dietary foods in a glycosylated form, which prevents resveratrol from enzymatic oxidation in the digestive tract, thus preserving its biological activity and overall stability. 148 , 149 However, intestine cells absorb only resveratrol aglycone via transepithelial diffusion with an absorption rate of approximately 75%. Pharmacokinetics studies have confirmed that resveratrol is rapidly and comprehensively metabolized through the intestine and liver, and the main glucoside and sulfate metabolites of resveratrol are produced through glucuronidation and sulfation.…”
Section: Pharmaceutical Properties Of Resveratrol Against Endometriosismentioning
confidence: 99%
“…C Makgoelli brewing with red ginseng starch. and health benefits of rice wine, Yang et al(2019) bioprocessed the production of resveratrol-enriched rice wine by incorporating piceid and resveratrol from Polygonum cuspidatum roots (For chemical structures of resveratrol (3,5,4'-trihydroxystilbene) and trans-Piceid, see Figure 7). The authors documented the conversion of piceid to resveratrol by β-glucosidase enzyme during fermentation.…”
Section: Park Et Al (2018)mentioning
confidence: 99%
“…(i) Putrescine and tyramine were detected in high concentrations on the third day of storage at 20 °C Kim et al (2011). (ii) The concentration of tyramine increased rapidly during 5th day of storage at 20 °C.Bioactive phenolic compounds: (Piceid and Resveratrol) †(i) The quality of resveratrol-enriched rice wine was unaltered during four weeks of storage peroid under normal refrigeration temperatures (4 °C).Further studies are necessary on composition of Makgeolli under ambient conditions Yang et al (2019). (ii) The resveratrol-enriched rice wine had enhanced antioxidant and radical scavenging activity.…”
mentioning
confidence: 99%
“…The results showed that POPEP (POPE hydrolyzed by pepsin), with a molecular weight of 3-5 kDa, had the strongest antioxidant activity. Excessive free radicals or reactive oxygen species (ROS) are harmful to the human body since these components may destroy the normal functions of cells, tissues, and organs [12]. Superoxide dismutase, glutathione peroxide, and catalase can remove free radicals to reduce the risk of oxidative damage during periods of increased ROS.…”
mentioning
confidence: 99%